2006
DOI: 10.1021/ja063123d
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylated Cyclic Pentaalanine Peptides as Template Structures

Abstract: The N-methylation of cyclic peptides can be used to modify the activity and/or selectivity of biologically active peptides. As N-methylation introduces different flexibility and lipophilicity, it can also improve the bioavailability (the ADMET profile). To search for conformationally constrained cyclic peptides, a library of 30 different N-methylated peptides with the basic sequence cyclo(-D-Ala-L-Ala4-) was synthesized. Based on the NMR analysis, seven of these peptides exhibited single conformations (>98%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
121
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 87 publications
(71 reference statements)
11
121
0
9
Order By: Relevance
“…This result gives an indication of the importance of the spatial orientation of Phe 11 . Although there is a loss in the bent conformation by Nmethylation of Phe 11 which results in the deep burying of the phenyl ring, it retains an activity comparable to the stem peptide. These results suggest that multiple N-methylation can also be useful in elucidating fine details of the bioactive conformation.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…This result gives an indication of the importance of the spatial orientation of Phe 11 . Although there is a loss in the bent conformation by Nmethylation of Phe 11 which results in the deep burying of the phenyl ring, it retains an activity comparable to the stem peptide. These results suggest that multiple N-methylation can also be useful in elucidating fine details of the bioactive conformation.…”
mentioning
confidence: 77%
“…[17] In general, we observe an enhancement in the binding affinity when the molecule contains MeLys 9 and a reduction with Me-d-Trp 8 or MePhe 11 , this subtle modulation in the activity could be understood by analyzing the conformations of these analogues. Goodman et al suggested the bent conformation of the peptide as the bioactive conformation, which is stabilized by the two g turns about Phe 7 and Thr 10 .…”
mentioning
confidence: 85%
See 3 more Smart Citations